Estimating and modeling the dynamics of the intensity of infection with Schistosoma japonicum in villagers of Leyte, Philippines. Part II: Intensity-specific transmission of S. japonicum. The schistosomiasis transmission and ecology project - Riley, S.; Carabin, H.; Marshall, C.; Olveda, R.; Willingham, Arve Lee; McGarvey, S.T. (2005)
A dynamic model of Schistosoma japonicum transmission is presented that incorporates effects of infection intensity, age, and sex. We use four infection intensity classes to investigate the impact of ecologic changes and public health interventions on the burden of infection within communities. Age- and sex-specific infection data from three disease-endemic villages in the Philippines are used to estimate the parameters of the model. The model gives good qualitative agreement with observed fecal egg counts adjusted for the accuracy of the Kato-Katz examination. Our results suggest that differences in infection burden between villages are caused by differences in both the infection process and the recovery process in humans. We describe the potential impact of mass treatment of all humans on the numbers with high infection. Furthermore, we show that a sudden reduction in snail population size would affect high prevalence and low prevalence communities in different ways.